Organic crops or energy crops? Options for rural development in Cambodia and the Lao People's Democratic Republic - Anil Markandya; Sununtar Setboonsarng (Asian Development Bank Institute (ADBI), 2008)
This paper examines the prospects for organic agriculture (OA) and the production of biofuels as strategies for rural development in Cambodia and the Lao People's Democratic Republic (Lao PDR). Both agricultural activities are growing worldwide, although there are some questions as to how effective they are, environmentally and socially. These questions are discussed in the first part of the paper. The second part looks in detail at the potential for OA and biofuels in the two countries. The benefits of both activities in terms of poverty reduction and environmental sustainability to developing countries such as Cambodia and the Lao PDR are likely to be significant, although the full extent of that is subject to market access (particularly for organic foods) and the costs of certification. Poverty impacts appear to be greater for OA than for biofuel but since the growing areas do not generally overlap, both could be promoted. Since the present agricultural environment in both countries is generally regarded as 'clean' with a low level of chemical inputs, production of safe food for a high-value market may be a preferred strategy than to intensify agriculture through conventional methods and compete with more developed countries. Assistance from external organizations in overcoming challenges will be critical for the success of any programs to promote both OA and biofuels.
Keywords: Q01; Q12; Q17; Q18; 330; Ökologischer Landbau; Biokraftstoff; Ländliche Entwicklung; Kambodscha; Laos